Improving Passing Skills Football through Playing Approach: Action Research Students of SD Karya Makmur I Karawang - Pangestu, Gilang Dwi (Journal of Primary Education, 2023)
This study aims to improve football passing skills in Karya Makmur I Karawang Elementary School students. The research method used is action research from Kemmis and Taggart. The research subjects in this study were Karya Makmur I Karawang Elementary School students totaling 22 students. The research instrument used an inner leg passing test instrument that assessed the movement process. The data analysis technique used is descriptive qualitative and quantitative with a percentage form. The results showed that the average student score was 81 with a percentage of success of 95.4%. These results show that there has been a significant increase and the success criteria have been achieved, so the research was stopped in cycle II. The conclusion of this study is that the playing approach is effective and efficient in improving soccer passing skills in Karya Makmur I Karawang Elementary School students.